Camera Based Automated Quality Assessment of Fruits for a Smart Home - Thulaseedharan, Athulya; Choudhary, Ayesha (Proceedings of ... IEEE International Conference on Service Operations and Logistics, and Informatics, 2022)
A camera-based fruit quality system is essential for the smart home. In this work, we propose a fruit detection system based on their qualities. Sorting fruits by humans is a time-consuming process, subject to inconsistencies and influenced by surrounding conditions. In this camera-based fruit quality assessment system, the fruits are detected and predicted under qualities like Fresh and Rotten. In the system, the Camera module captures the image of the fruit and then sends it to the Quality Assessment module. In this module, the information from that image is extracted and tested based on YOLOv5. After detecting the quality, the system indicates to the the user whether the fruit is fresh or rotten. This helps the user to easily get to know about the quality of the fruit and can segregate the fruits according to their freshness. This automatic fruit handling system helps every user in a smart home to save time and buy better quality fruits.